Learning Speaking Problems in Online Learning During Covid-19 Outbreak for ESP Learners - Romadhon Romadhon (Journal of English Education, Literature and Linguistics, 2023)
Because of the pandemic, Indonesian government implemented new policies in the education system. Previously, education and training took place in the luring situation on a regular basis, particularly in higher education institutions, and now it is entirely daring. The current study aims to examine students' issues in speaking for ESP contexts during the COVID-19 circumstance when they were learning the English language by the online situation. The descriptive qualitative design was used in this study. The information was gathered using questionnaire in the help of Google form media and also interviews with 40 students from the fourth semester of the Management Informatics Diploma Major at Piksi Input Serang Polytechnic in Banten. Based on this study, the research findings highlighted a variety of issues for students. Six issues emerged during distance learning in the Speaking course. The first issue that arose was students' learning equipment and supporting facilities. The second issue was dealing with students' accessibility restrictions to Online Video Conference. The third issue was students' concerns on the lecturer's materials during an online lesson. The fourth issue was the students' approach to completing the lecturer's task or assignment. The use of online streaming videos as a media of learning resources also had a role in the fifth and final issue that emerged during distance learning amid COVID-19 pandemic situations is students' limited cell signal and internet quota. The findings can be used to further enhance and improve online teaching and learning techniques. Further research into how students deal with obstacles is encouraged.